Sekolah dari Lereng Pegunungan: Diversifikasi Layanan Pendidikan Nonformal Berbasis Musholla di Kampung 17, Batu Lawang, Cianjur - Vemmi Kesuma Dewi, Raden Roro; Rahmianti, Siti; Lituhayu, Asri Andriana (STIT Sirojul Falah Bogor, 2025)
Abstract: Kampung 17, a remote highland village in Batu Lawang, Cianjur, presents a challenging educational landscape. Isolated by valleys and steep ravines, children face severe difficulties accessing formal schools, which are located far and are hard to reach. The community’s low socioeconomic status, combined with limited electricity and infrastructure, exacerbates these constraints. This phenomenon underscores the urgent need for diversified nonformal education services that can reach and empower children in this area. This study examines the implementation of a nonformal education model based at Musholla Baitul Muttaqien as a